The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1080/10473289.2003.10466297
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Concentrations of Indoor Nitrogen Dioxide in Barcelona, Spain

Abstract: Sources and concentrations of indoor nitrogen dioxide (NO 2 ) were examined in Barcelona, Spain, during 1996Spain, during -1999. A total of 340 dwellings of infants participating in a hospital-based cohort study were selected from different areas of the city. Passive filter badges were used for indoor NO 2 measurement over 7-30 days. Dwelling inhabitants completed a questionnaire on housing characteristics and smoking habits. Data on outdoor NO 2 concentrations were available for the entire period of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Unfortunately, daily outdoor NO 2 values were not available for each of the days of indoor measurements and an extensive evaluation of outdoor contributions could not be investigated. Nonetheless, a study by Garcia‐Algar et al. (2003) showed a significant correlation between outdoor and indoor NO 2 concentrations in Barcelona confirming that outdoor pollution affects NO 2 concentrations in human dwellings.…”
Section: No2 Concentrationsmentioning
confidence: 84%
See 1 more Smart Citation
“…Unfortunately, daily outdoor NO 2 values were not available for each of the days of indoor measurements and an extensive evaluation of outdoor contributions could not be investigated. Nonetheless, a study by Garcia‐Algar et al. (2003) showed a significant correlation between outdoor and indoor NO 2 concentrations in Barcelona confirming that outdoor pollution affects NO 2 concentrations in human dwellings.…”
Section: No2 Concentrationsmentioning
confidence: 84%
“…Data on mean yearly outdoor NO 2 concentrations measured by fixed monitoring stations through a chemiluminescent analyzer (Garcia‐Algar et al., 2003) were available in the three centers.…”
Section: Study Populationmentioning
confidence: 99%
“…Data collection methods are critical to the efficiency of population studies. Questionnaire-based study methods have been used in previous studies investigating occupant health and safety [3-7]. In today's communication society, web-based methods appear to be a natural development of methodology.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in agreement with many studies. Another study by García‐Algar et al. (2003) showed that, with each ppb increase in outdoor NO 2 , there was a 1% increase in indoor concentrations.…”
Section: Discussionmentioning
confidence: 95%
“…This finding is in agreement with many studies. Another study by -Algar et al (2003) showed that, with each ppb increase in outdoor NO 2 , there was a 1% increase in indoor concentrations. It should also be noted that, as the passive diffusion tubes were placed in back porches, which were quite close to the home, there could be some indoor NO 2 influencing the outdoor levels.…”
Section: Discussionmentioning
confidence: 97%